1994
DOI: 10.1071/pp9940475
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between CO2 Transfer Conductance and Leaf Anatomy in Transgenic Tobacco With a Reduced Content of Rubisco

Abstract: The CO2 transfer conductance in leaves quantifies the ease with which CO2 can diffuse from sub-stomatal cavities to sites of carboxylation within the chloroplast. The aim of this work was to test the hypothesis that the CO2 transfer conductance is proportional to the surface area of chloroplasts exposed to intercellular airspaces. We compared two genotypes, wild-type and transgenic tobacco, that had been transformed with an antisense gene directed at the mRNA of the Rubisco small subunit. Transgenic tobacco ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
455
4
4

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(485 citation statements)
references
References 0 publications
22
455
4
4
Order By: Relevance
“…Under our growth conditions Rubisco constituted approximately 12 to 15% of the leaf soluble protein in the F. bidentis control plants, one-half of what is normally observed in C, plants (e.g. Evans et al, 1994). This is consistent with previous observations that the C4 species use nitrogen more efficiently than Figure 3 .…”
Section: Discussion Antisense Effect On Leaf Biochemistry and Photosysupporting
confidence: 81%
“…Under our growth conditions Rubisco constituted approximately 12 to 15% of the leaf soluble protein in the F. bidentis control plants, one-half of what is normally observed in C, plants (e.g. Evans et al, 1994). This is consistent with previous observations that the C4 species use nitrogen more efficiently than Figure 3 .…”
Section: Discussion Antisense Effect On Leaf Biochemistry and Photosysupporting
confidence: 81%
“…These values are about 5 times greater than published measurements made in other species based on transmission electron microscopy (Evans et al, 1994;Moghaddam and Wilman, 1998;Hanba et al, 2002;Scafaro et al, 2011). LM measurements of cell wall thickness might be affected by optical artifacts (blurring near the limit of optical resolution might increase apparent wall thickness) or sampling artifacts (e.g.…”
Section: Unknown Parameterscontrasting
confidence: 43%
“…Transgenic plants with reduced photosynthesis showed that g s was largely unaffected Stitt et al, 1991;Hudson et al, 1992;Evans et al, 1994;Price et al, 1998), thereby breaking the long-standing correlation between A and g s that is usually conserved. More recent studies have similarly demonstrated that g s and A can be uncoupled when carbon fixation via Rubisco (von Caemmerer et al, 2004) and electron transport (Baroli et al, 2008) are down-regulated.…”
Section: Engineering Stomatal Signaling and Metabolismmentioning
confidence: 99%